Hyperbaric oxygen therapy attenuates heatstroke-induced hippocampal injury by inhibiting microglial pyroptosis - Ancong Xu; Fan Huang; Er Chen; Zhiqiang Zhang; Yanxuan He; Xichong Yu; Guoxin He (International Journal of Hyperthermia)
Background: Central nervous system (CNS) injury is the most prominent feature of heatstroke and the hippocampus is prone to damage. However, the mechanisms underlying the heatstroke-induced hippocampal injury remain unclear. Hyperbaric oxygen (HBO) therapy prevents CNS injury in heatstroke mice. However, the underlying mechanisms of HBO in heatstroke-induced hippocampal injury remain unclear. This study aimed to elucidate the protective effects of HBO against hippocampal injury and its potential role in microglial pyroptosis in heatstroke rats.Methods: A rat heatstroke model and a heat stress model with a mouse microglial cell line (BV2) were, respectively, used to illustrate the effect of HBO on heat-induced microglial pyroptosis in vivo and in vitro. We used a combination of molecular and histological methods to assess microglial pyroptosis and neuroinflammation both in vivo and in vitro.Results: The results revealed that HBO improved heatstroke-induced survival outcomes, hippocampal injury, and neurological dysfunction in rats. In addition, HBO mitigates microglial pyroptosis and reduces the expression of pro-inflammatory cytokines in the hippocampus of heatstroke rats. In vitro experiments showed that HBO attenuated BV2 cell injury under heat stress. Furthermore, HBO prevented heat-induced pyroptosis of BV2 cells, and the expression of pro-inflammatory cytokines IL-18 and IL-1β was reduced. Mechanistically, HBO alleviates heatstroke-induced neuroinflammation and hippocampal injury by preventing microglial pyroptosis. Conclusions: In conclusion, HBO attenuates heatstroke-induced neuroinflammation and hippocampal injury by inhibiting microglial pyroptosis.